(untitled) (UCC Law Journal, 2025)
Negotiation is a very vital tool for resolving disputes amicably and ensuring harmony in international relations. Further, it is the process of engaging in ‘dialogues or discussions’ with the sole object of reaching an acceptable agreement by the parties involved in a dispute. Essentially, negotiation aims to achieve fairness and security among states. It is voluntary, non-adjudicative, informal and flexible. This article seeks to identify and analyse the challenges and limitations African countries face in negotiating with international bodies and other countries as well as propose strategies, approaches and attitudes they must adopt to ensure a more favourable negotiation outcome. The paper is divided into eight sections, which are based on secondary data analysis and literature review that covers the area of study in addition to other theoretical and legislative enactments on international negotiation in Africa. The review of the literature examined information from several important sources which covers the major area of the paper.